2021
DOI: 10.3390/vehicles3020017
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Assessment of Parking Constraints for Automated Mobility on Demand: A Case Study of Zurich

Abstract: In a coordinated mobility-on-demand system, a fleet of vehicles is controlled by a central unit and serves transportation requests in an on-demand fashion. An emerging field of research aims at finding the best way to operate these systems given certain targets, e.g., customer service level or the minimization of fleet distance. In this work, we introduce a new element of fleet operation: the assignment of idle vehicles to a limited set of parking spots. We present two different parking operating policies gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, planning studies also focus on interactions between AMoD systems and existing infrastructure. Aspects of interest include the allocation of parking space (48,49), the optimal placement of charging stations, charge scheduling for electric AVs (50)(51)(52)(53)(54), contributions to congestion (55), joint operation with other modes of transportation (56,57), autonomous calibration (58), smart infrastructure (59), and the achievable performance of the overall mobility system (45).…”
Section: Interactions With Existing Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, planning studies also focus on interactions between AMoD systems and existing infrastructure. Aspects of interest include the allocation of parking space (48,49), the optimal placement of charging stations, charge scheduling for electric AVs (50)(51)(52)(53)(54), contributions to congestion (55), joint operation with other modes of transportation (56,57), autonomous calibration (58), smart infrastructure (59), and the achievable performance of the overall mobility system (45).…”
Section: Interactions With Existing Infrastructurementioning
confidence: 99%
“…Parking policies typically relocate idling AVs while not causing deterioration in metrics such as waiting times, distance traveled, and congestion. In graph-theoretic models, effects of parking are captured by additional costs when idling at a node (price of parking) (11,100,101) or via upper bounds on the number of AVs at a node (capacity of parking lots) (48,69,70,74). In queuing-theoretic models, stations are usually assumed to have an infinite number of parking spaces (82).…”
Section: Parkingmentioning
confidence: 99%
“…Therefore, planning studies also focus on interactions between AMoD systems and existing infrastructure. Aspects of interest include allocation of parking space (48,49), optimal placement of charging stations, charge scheduling for electric AVs (50,51,52,53,54), contribution to congestion (55), joint operation with other modes of transportation (56,57), autonomous calibration (58), smart infrastructure (59), and achievable performance of the overall mobility system (45).…”
Section: Design Of Av Fleetsmentioning
confidence: 99%
“…Parking policies typically relocate idling AVs, while not deteriorating metrics such as waiting times, traveled distance, and congestion. In graph-theoretic models, effects of parking are captured by additional costs when idling at a node (price of parking) (11,100,101) or via upper bounds on the number of AVs at a node (capacity of parking lots) (48,69,70,74). In queueing-theoretic models, stations are usually assumed to have infinite parking spaces (82).…”
Section: Operational Constraintsmentioning
confidence: 99%
“…The study found that the system can function successfully even when there are a limited number of parking spaces available, and that expanding capacity of parking by one parking place per automobile cannot provide any advantages. Furthermore, it ensures optimum parking spaces' distribution for a certain on-demands and city transportations system [2].…”
Section: Introductionmentioning
confidence: 99%